Supratentorial Brain Tumors in Children - Zikou, Anastasia K.; Xydis, Vassileios; Alexiou, George; Argyropoulou, Maria I. (Journal of Pediatric Neuroradiology, 2016)
Brain tumors in children are the second most common type of pediatric tumors after leukemia and the most common occurring solid tumor. Brain tumors diagnosed during the first year of life have different features than those presenting later in childhood and are usually supratentorial. Magnetic resonance imaging is the modality of choice for the diagnosis and characterization of these tumors. Herewith, we provide a review of the imaging characteristics on conventional and advanced neuroimaging techniques of the most common supratentorial intracranial tumors in children.
Keywords: children; brain tumor; supratentorial